MINNESOTA LEGISLATIVE STATUS - BROZEK, MICHAEL (Tufts Archival Research Center, 2007)
Marginalia; Letter to Roger Mozingo from Michael Brozek regarding the status of Minnesota legislation on tobacco. Gives the background of legislation in Minnesota and then lists all the pending bills and their content as well as industry activity in combating the bill.